Maintenance Strategies and Life Cycle Costs of Renewable Energy Systems - Kocsis, Imre; T. Kiss, Judit; Deák, Krisztián (International Journal of Engineering and Management Sciences, 2018)
Life cycle costs are important factors in decisions on renewable energy investments. Since maintenance costs generally constitute a high portion of the life cycle costs, the maintenance strategy applied in a project can affect the bottom line significantly. The effective maintenance tools used in the production industry (e.g., diagnostics, condition monitoring, data management, integrated information systems, machine learning, and automated decision making) can be involved in planning and maintenance of renewable energy systems to gain the benefits of these approaches. In this paper the effects of maintenance strategies on life cycle costs are investigated and the benefits of up-to-date condition monitoring techniques are presented through case studies.